Proteomics identification of novel fibrinogen-binding proteins of Streptococcus suis contributing to antiphagocytosis - Pian, Yaya; Wang, Pingping; Liu, Peng; Zheng, Yuling; Zhu, Li; Wang, Hengliang; Xu, Bin; Yuan, Yuan; Jiang, Yongqiang (Frontiers in Cellular and Infection Microbiology, 2015)
Streptococcus suis serotype 2 (SS2) induced sepsis and meningitis are often accompanied by bacteremia. However, the mechanism whereby it helps S. suis to evade PMN-mediated phagocytosis remain unclear. Because of the central roles of bacteria-human fibrinogen (hFg) interaction in innate immunity, here, a proteomics based Far-western blotting (PBFWB) was developed to identify the fibrinogen-binding surface proteins of S. suis (SsFBPs) on a large-scale. And then thirteen potential SsFBPs were identiﬁed by PBFWB and we selected seven potential surface proteins to further confirm their binding ability to hFg, of which the gene mutant strains of MRP displayed significantly decrease in binding to immobilized hFg. Additionally, the polyclonal antibodies against Enolase were found to significantly inhibit the binding of SS2 to hFg. Strikingly, MRP and Enolase were found to improve the antiphagocytic ability of SS2 to PMNs by interacting with hFg and enhance the survival of SS2 in human blood. Taken together, the PBFWB method provides useful clues to the bacteria-host interactions. These studies firstly disclose MRP and Enolase were involved in immune evasion of SS2 at least in part by binding to Fg, which make them potential targets for therapies for SS2 infection.